Blueprint as A Base In Building Better Teacher- Made Test - Milawati Milawati (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2019)
Teacher made test becomes popular in most rural nor urban school, since multiple learning develop simultaneously during an educational experience. However, teacher often reuse tests without analysing or revising them and seldom use statistical procedures to see how a test or a test item is actually performing. Assesing students often means reaching for a test or quiz that is already prepared, whether it be a test included a textbook or something another teacher prepared. These are not neccessarily bad choices, but to make sure they are good choices, the knowledgeable about the blueprint in making a teacher made test should be known. This paper presents seven cornerstones of assessment, how to plan  and how to make a teacher made test blueprint. Knowing more about those issue will not only help the teacher to assess the students more effectively, but it will also provide the teacher with a means of evaluating the teaching learning process and help the teacher to produce test that will actually motivate the students to learn.